PERANCANGAN BRANDING SONGKET SILUNGKANG - Riki Iskandar; Rosta Minawati; Martion Martion (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT The title of this final project is “Designing the Branding of Songket Silungkang.” The purpose of the designing is to get identity which is always remembered so that it changes the behavior of targeted audience. Even though the city government has managed and organized the weavers, the songket weavers in the outside of Silungkang area also want to create the songket name according to the names of their areas. Therefore in the design of this songket Silungkang branding, it is highlighted through verbal and visual messages which are effective and efficient.The media of its design was the logo along with its description. The application of this media was in the forms of poster, x-banner, banner, flag-change, bumper logo, pin, sticker, key chain, postcard, billboard, brochure and facebook cover. All those media were the part of songket Silungkang branding process. Keywords: Designing, Branding, Songket, Silungkang